Spatial manipulation of cells and organelles using single electrode dielectrophoresis. (January 2012) - Graham, David M.; Messerli, Mark A.; Pethig, Ronald
The selection, isolation, and accurate positioning of single cells in three dimensions are increasingly desirable in many areas of cell biology and tissue engineering. We describe the application of a simple and low cost dielectrophoretic device for picking out and relocating single target cells. The device consists of a single metal electrode and an AC signal generator. It does not require microfabrication technologies or sophisticated electronics. The dielectrophoretic manipulator also discriminates between live and dead cells and is capable of redistributing intracellular organelles.